Prawo do dobrej administracji — w kierunku upraszczania języka urzędowego w Polsce i w Czechach - Kocowska-Siekierka, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper aims at investigating how European Union countries such as Poland and the Czech Republic deal with the problem of simplification of the official language. In former members of the Eastern European bloc bureaucratic language is one of the causes of the loss of confidence in public administration. Entry to the European Union increased the tendency for language reform in the creation of normative acts, and the way of communication between the civil servants and thecitizens. The paper presents two lines of action — education of civil servants in Poland and the transformation of the legal language in the Czech Republic.
Keywords: prawo do dobrej administracji; Polska; Czechy; upraszczanie języka urzędowego